The Role of Extra-Campus Organization in Building "Bela Negara" Character: Case of Cipayung Group of East Java - Sri Wibawani; Anis Rosella Pitaloka; Luluk UI Magnun; Roiyanatun Mahbubah; Jojok Dwiridotjahyono (Journal of Economics, Business, and Government Challenges, 2020)
This study aims to explore the role of the Extra-Campus Student Organizations incorporated in the Cipayung Group, namely: Indonesian National Student Movement (GMNI), Indonesian Islamic Student Movement (PMII), Indonesian Student Association (HMI), Indonesian Christian Student Movement (GMKI) ), and the Catholic Students Association of the Republic of Indonesia (PMKRI) in raising awareness of the nation defense in East Java. This study uses a qualitative approach with data collection techniques in the form of content analysis of credible news, in-depth interviews, and focus group discussions (FGD) on informants or informants selected based on purposive techniques. The data analysis technique used is an interactive model, and the data validity test technique uses triangulation. The results of this study indicate that the Copying Group in terms of regeneration implanted the values of the country's defense through compulsory material delivered in activities ranging from member recruitment, primary education and training, and further training. In terms of scientific studies and issues, the Copying Group often conducts study discussions that also carry the theme of defending the country. In terms of student actions or movements, the values of state defense instilled through efforts to criticize government policies that are considered non-Pancasila. Copying Group members also carry out community service which aims to instill in their members that love for the motherland and willingness to sacrifice for the nation and state. Then it can be concluded that the Copying Group has a role in raising awareness of the defense of the student state in East Java.